2019
DOI: 10.1177/1559325818820649
|View full text |Cite
|
Sign up to set email alerts
|

Serum 8-Hydroxy-2′-Deoxyguanosine Level as a Potential Biomarker of Oxidative DNA Damage Induced by Ionizing Radiation in Human Peripheral Blood

Abstract: In this study, the effect of ionizing radiation on 8-hydroxy-2′-deoxyguanosine (8-OHdG) in human peripheral blood was investigated. Blood samples were collected from 230 radiation workers and 8 patients who underwent radiotherapy for population study. Blood samples from 2 healthy individuals were irradiated with different X-ray doses for in vitro experiment, and levels of 8-OHdG in serum and cell culture supernatants were assessed by enzyme-linked immunosorbent assay. Observations demonstrated the positive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 34 publications
(41 reference statements)
0
40
0
Order By: Relevance
“…Gao and his colleagues 23 demonstrated that serum 8-OHdG levels were significantly elevated in interventional radiologists compared with other categories of radiation workers, highlighting that the extend of oxidative DNA damage is proportional to the radiation dose. In other words, increasing radiation doses result in a more severe oxidative DNA damage, thereby indicating a distinct dose-response relationship.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gao and his colleagues 23 demonstrated that serum 8-OHdG levels were significantly elevated in interventional radiologists compared with other categories of radiation workers, highlighting that the extend of oxidative DNA damage is proportional to the radiation dose. In other words, increasing radiation doses result in a more severe oxidative DNA damage, thereby indicating a distinct dose-response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, there is another point of view regarding prolonged irradiation which primarily concerns cancer patients receiving radiotherapy; 8-OHdG levels not only can be decreased but also can be found lower than those of healthy subjects due to DNA repair mechanisms. 22,23 Gao and his colleagues 23 demonstrated that serum 8-OHdG levels were significantly elevated in interventional radiologists compared with other categories of radiation workers, highlighting that the extend of oxidative DNA damage is proportional to the radiation dose. In other words, increasing radiation doses result in a more severe oxidative DNA damage, thereby indicating a distinct dose-response relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An oxidized form of guanosine, 8-OHdG, is a biomarker of oxidative DNA damage and is involved in the pathology of many diseases such as cancer, atherosclerosis, and diabetes [ 3 ] . Base excision DNA repair pathway recognizes 8-OHdG as a threatening lesion, which results in its excretion in human urine without further metabolism [ 4 ] .…”
Section: Introductionmentioning
confidence: 99%